The Effect of Aerobic Exercise on Brain-Derived Neurotrophic Factor in People with Neurological Disorders: A Systematic Review and Meta-Analysis - Christopher P. Mackay; Suzanne S. Kuys; Sandra G. Brauer (Neural Plasticity)
Objective. To determine the effect of aerobic exercise on brain-derived neurotrophic factor (BDNF) levels in people with neurological disorders. Data Sources. Six electronic databases (CINAHL, PubMed, Cochrane, PsycINFO, SportDiscus, and Web of Science) were searched until the end of December 2016. Study Selection. Experimental or observational studies of people with neurological disorders who undertook an exercise intervention with BDNF as an outcome measure. The search strategy yielded 984 articles. Data Extraction. Study data were independently extracted from each article. Methodological quality of studies was assessed using the Physiotherapy Evidence Database (PEDro) scale. A meta-analysis was planned based on the assessment of predetermined criteria. Data Synthesis. Eleven articles were included. Studies employed either a program of aerobic exercise, a single bout of aerobic exercise, or both. A meta-analysis of studies comparing a program of aerobic exercise against usual care/nil therapy showed a large effect (SMD: 0.84, 95% CI 0.47–1.20, p<0.001) in favour of aerobic exercise to increase levels of BDNF. Findings for a single bout of aerobic exercise were mixed. Quality of studies was low (PEDro average score 4.3/10). Conclusions. A program of aerobic exercise may contribute to increased levels of BDNF in neurological populations.